Sociocultural approach to learning to speak English - Levchenko, Yana (Educational Challenges, 2025)
Purpose/Aim. This study investigates how sociocultural factors influence the process of learning to speak, with a focus on the interaction between learners and their social environments. The rationale stems from the need to understand language acquisition as a socially situated activity rather than a purely individual cognitive process. The paper also examines the impact of cultural identity, motivation, and community participation on language learning outcomes It is emphasized that the integration of the sociocultural component contributes to the development of interpersonal communication skills, understanding the norms and values of native speakers, and also increases motivation to learn a foreign language. Drawing on the sociocultural theories, the study highlights how communication in authentic settings, peer interaction, and scaffolding contribute to developing speaking skills in learners of English. Social speech, private speech, and inner speech are discussed as developmental stages in the internalization process, where learners move from guided conversation to self‑regulated use of English. The findings suggest that integrating sociocultural principles into English language teaching can enhance learners’ communicative competence and foster more meaningful engagement with the language. Methodology. The research employed a qualitative case study approach involving students in multilingual urban settings. Data were collected through non-participant observation, audio recordings of interactions, and semi-structured interviews with educators and students. Discourse analysis and thematic coding were used to analyze the interactions and identify recurring patterns of language learning. Results. Students’ speech development was significantly influenced by peer interactions and participation in culturally meaningful activities. Instances of guided participation and collaborative dialogue were more frequent in environments with structured routines and high adult involvement. Variability was noted in language output based on the students’ cultural backgrounds and their roles in the group. Conclusions. The findings support the sociocultural theory that speech development is mediated through social interaction and cultural tools. Learning to speak is not only a cognitive task but also a relational and contextual one. Future research should examine the role of digital tools and transnational cultural practices in shaping early language experiences.